PEMANFAATAN APLIKASI STANDAR PERTUMBUHAN WHO 2005 BERBASIS SMARTPHONE ANDROID (PSG BALITA) TERHADAP KUALITAS DATA GIZI - Al Rahmad, Agus Hendra; Junaidi, Junaidi (Politeknik Kesehatan Tanjung Karang, 2020)
The importance of fulfilling nutritional status information based on individuals can be fulfilled by using an online application system for recording and reporting community-based nutrition. The need for interventions to support nutritional surveillance through nutritional status monitoring activities can be carried out by name by address. The research objective was to make an assessment using a PSG Balita software can improve data and information quality of nutritional status. A quasi-Experimental research design needs to be done with Electronic and manual intervention on two districts involving 24 nutritionists at the public health center. Primary and secondary data was collected through an interview and observations using a questionnaire. The training in the treatment group by using the tool a PSG Balita Software, and the control group used the book Kepmenkes RI No:1995/Menkes/SK/XII/2010. Information quality analysis is dependent on t-test and independent t-test, using the R. Intervention results of each group indicate increase the quality of nutrition information status (p-value<0,05). Group intervention use who anthro showing increased better (p-value<0,05) than manual intervention. Besides, recording and reporting outputs model based on electronics can release more information, and useful in nutrition program planning, monitoring, and evaluation. The use of electronic-based systems is better quality and more data analysis outputs, both for monitoring planning and nutrition program evaluation as well as decision-making support.